Caracterização das espécies de leishmania em sangue periférico de cães por PCR-RFLP NA área endêmica de Bauru/SP - Sanches, Letícia da Cruz [UNESP] (2014)
Leishmaniasis is a major public health problem in the world. The protozoa of the genus Leishmania has worldwide distribution and epidemiology of the disease depends on the characteristics of the parasites. Leishmaniasis are divided into visceral leishmaniasis and cutaneous. The dog plays a key role in the transmission of L. infantum to humans and in the epidemiology of the disease. Due to the adaptation of Leishmania to new hosts or vectors is important to know the current etiologic agent in dogs. Molecular techniques have been used for the diagnosis of leishmaniosis. The PCR-RFLP detects and distinguishes the different species of the parasite. The objective of this study was to identify the Leishmania species found in 103 samples of peripheral blood of dogs naturally infected with this protozoan, the city of Bauru - SP. For the diagnosis of leishmaniosis was determined by parasitological examination, indirect ELISA and PCR was performed. The determination of Leishmania species the DNA amplified intergenic region ITS1 was digested with the restriction enzyme HaeIII. Positive samples for Leishmania ssp. showed an identical restriction profile of L. amazonensis in 77/103 samples, 17/103 were similar to L. infantum, and 09/103 were mixed profile. In conclusion, we identified L. amazonensis greater number of dogs than L.infantum in Bauru city, SP